Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from MIRAI in the South Atlantic Ocean from 2003-11-06 to 2003-12-05 (NCEI Accession 0144246) ... - Uchida, Hiroshi; Fukasawa, Masao; Murata, Akihiko (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway data collected from MIRAI in the South Atlantic Ocean from 2003-11-06 to 2003-12-05. These data include AIR TEMPERATURE, BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - atmosphere, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY, SEA SURFACE TEMPERATURE, WIND DIRECTION and WIND SPEED. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Akihiko Murata of Meteorological Research Institute as part of the CLIVAR_A10_2003_Underway dataset. CDIAC associated the following cruise ID(s) with this dataset: 49NZ20031106 The International CLIVAR Global Ocean Carbon and Repeat Hydrography Program carries out a systematic and global re-occupation of select WOCE/JGOFS hydrographic sections to quantify changes in storage and transport of heat, fresh water, carbon dioxide (CO2), and related ...